Surface Engineering of Graphene - Sahoo, Sumanta; Tiwari, Santosh Kumar; Nayak, Ganesh Chandra (Carbon Nanostructures,, 2019)
This book presents the state of the art in the processing, properties, and applications in various fields of science and technology related to graphene and its derivatives. It also discusses the limitations and drawbacks of graphene due to some of its intrinsic properties. Further, it provides a brief overview of graphene analogs, comparing the properties of graphene with those of other similar 2D materials.